If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5.95 = 2.95 + 0.05x Solving 5.95 = 2.95 + 0.05x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.05x' to each side of the equation. 5.95 + -0.05x = 2.95 + 0.05x + -0.05x Combine like terms: 0.05x + -0.05x = 0.00 5.95 + -0.05x = 2.95 + 0.00 5.95 + -0.05x = 2.95 Add '-5.95' to each side of the equation. 5.95 + -5.95 + -0.05x = 2.95 + -5.95 Combine like terms: 5.95 + -5.95 = 0.00 0.00 + -0.05x = 2.95 + -5.95 -0.05x = 2.95 + -5.95 Combine like terms: 2.95 + -5.95 = -3 -0.05x = -3 Divide each side by '-0.05'. x = 60 Simplifying x = 60
| (2x-7)-(x-15)=14 | | 8.55=1.55+10x | | 3(x-(4x+14))=5 | | 3(x-(4x-14))=5 | | 13-3x=2-(7x+5) | | A=-7.5-2a^2 | | -2(x-2)=8 | | C^2-8c+15=0 | | C^2-8c=-15 | | y=40x-5x | | Z^2+8z=0 | | 16x^3+36x^2= | | X+(2x+0.15)+(x+0.05)=1.8 | | 5y-4=5 | | -5(-7)(-3)= | | 4v-5=z | | 2n+(13+n)+n=93 | | 136-(6x+16)=6(x+7)+x | | x-2=-8 | | -2(3s-4)-8=-3(6s+1)-5 | | -4x-7y=6 | | (2x-7)-(x-3)=2 | | 3a-4b=8b | | 2n+13+n=93 | | 2n+13n=93 | | 2x+4x-1=11 | | 2.91-(-0.2)= | | -7+(-32)-12+5= | | x^2-3=77 | | 6x-3(6x-3)=93 | | .08(24)+.02x=.04(12+x) | | 5-2x=4x+41 |